An intelligent HAZOP quantitative analysis method based on deviation duration. Issue 1 (2nd June 2019) - Zhou, Guang‐Wen; Yang, Xia; Zheng, Shi‐Qing; Cheng, Xi‐An
Abstract: The limit of deviation duration is regarded as an important evidence of the possibility of deviation bringing hazards to the system. And the limits of deviation duration are different when the different process parameters reaching the hazardous threshold (or design value) caused by the same deviation value. Furthermore, the sequence of hazards occurring in the system after generating deviations, that is, deviation transfer path, is formed by process parameters arranged in an ascending order based on the limit of the deviation duration and devices involved. T‐SDG model has been proposed after improving the SDG model, so as to show the deviation propagation path of quantitative analysis. Besides, the characteristics of deviation propagation has been researched; and the influence of simultaneous deviations on the system has been also analyzed in detail. Meanwhile, superposition effect, offset effect, and offset curve have been put forward in order to ensure the system security. Highlights: In this paper, a quantitative analysis method had been proposed. The definition of the deviation had been extended. The propagation path was researched based on when the parameters reaching the threshold. The influence of the simultaneous occurrence of multiple deviations on the system had researched.